Petroleum geology of the South Caspian Basin - Buryakovsky, Leonid A. (Gulf Professional Pub., 2001)
In this information-packed volume, the authors present mathematical models and analyses for evaluating, assessing, and describing the petroleum geology of the oil-rich South Caspian Sea Basin, including eastern Azerbaijan and western Turkmenistan. Their mathematical models include descriptions of the development and structure of the surrounding geological systems and traps. Details the petrophysical properties and interrelationship with reservoir and source rocks Describes how new technology has made it possible to profitably produce off previously useless wells A valuable resource for exploration companies in the area of the South Caspian Basin.